2017
DOI: 10.1016/j.hrthm.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of a transcatheter pacing system: 12-Month results from the Micra Transcatheter Pacing Study

Abstract: Long-term performance of the Micra transcatheter pacemaker remains consistent with previously reported data. Few patients experienced major complications through 12 months of follow-up, and all patient subgroups benefited as compared to transvenous pacemaker historical control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
181
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(210 citation statements)
references
References 16 publications
17
181
0
12
Order By: Relevance
“…Leadless pacemakers eliminate pocket‐related infections and have the potential to reduce lead‐related endocarditis. In the Micra leadless pacemaker investigational device exemption (IDE) study and post approval registry (PAR) no Micra device‐related infections or any infections requiring device removal were observed . Hence, Micra in the setting of device infection might be an appealing pacing alternative after CIED removal.…”
Section: Introductionmentioning
confidence: 99%
“…Leadless pacemakers eliminate pocket‐related infections and have the potential to reduce lead‐related endocarditis. In the Micra leadless pacemaker investigational device exemption (IDE) study and post approval registry (PAR) no Micra device‐related infections or any infections requiring device removal were observed . Hence, Micra in the setting of device infection might be an appealing pacing alternative after CIED removal.…”
Section: Introductionmentioning
confidence: 99%
“…Leadless pacemakers eliminate the need for a subcutaneous pocket and associated generator pocket infections. Interestingly, no cases of hematogenous device infections were seen either in any of the leadless pacemaker clinical trials 7–10 . Recently, a provocative clinical observation derived from the Micra transcatheter pacemaker IDE trial showed the absence of device infection in the setting of documented bacteremia or endocarditis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The early experience with a leadless pacemaker reported a 99% implant success rate, with 96% of patients free from major complication [72]. In a comparison between historical controls and leadless pacing implants, the relative risk of major complications was reduced by 48% with the leadless technology [73]. The data of the ‘real world’ MICRA leadless pacemaker have recently confirmed the short-term reliability of this type of device implant [74,75].…”
Section: The Future Of Electrical Therapies In Laminopathiesmentioning
confidence: 99%